Analysis of students' soccer shooting based on strength, coordination, and concentration - Ferdy Febriansyah; Khairudin Khairudin; Arsil Arsil; Aldo Naza Putra (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aimed to conduct a needs analysis for developing a football shooting training program by profiling lower-limb explosive power, foot–eye coordination, and concentration among extracurricular football students at SMKN 1 Sijunjung. Thirty students with at least six months of regular training participated in purposive sampling. Explosive power was assessed using the Vertical Jump Test, coordination with the Foot–Eye Coordination Test, concentration with the Grid Concentration Test, and shooting ability with a standardized shooting test. Data were analyzed descriptively, using normative categorization, gap analysis, and a Need Priority Index (NPI) to identify training priorities. Results showed most students scored low across lower-limb power (63%), coordination (58%), concentration (71%), and shooting ability (68%), with the largest gaps in concentration, explosive power, and coordination. The NPI indicated a structured, progressive training approach prioritizing mental focus, neuromuscular power, and coordination before technical shooting development. These findings provide empirical guidance for targeted, evidence-based interventions in youth football training.